The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1590/0001-3765201820170847
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and antibacterial activity of essential oils from Citrus aurantifolia leaves and fruit peel against oral pathogenic bacteria

Abstract: Tooth decay is a major public health problem which affects a large number of people in several countries. Even though more than 700 bacterial species have been detected in the oral cavity, Streptococcus and Lactobacillus stand out as the genera that cause tooth decay and other periodontal diseases. In this study, essential oils from Citrus aurantifolia leaves (CL-EO) and fruit peel (CP-EO) were obtained by hydrodistillation by a Clevenger-type apparatus whereas their chemical composition was analyzed by gas ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 24 publications
3
47
0
8
Order By: Relevance
“…However, the hexane extract was the only one that had low activity against bacteria whose MIC value was 1000 µg mL -1 (Table 2). Lemes et al (2018) have recently reported that MIC values below 100 µg mL -1 , between 100 and 500 µg mL -1 and between 500 and 1000 µg mL -1 correspond to promising, moderate and weak activities, respectively, whereas MIC values above 1000 µg mL -1 denote inactivity. Thus, it confirms the antibacterial potential of the most polar extracts from S. odoratissima leaves.…”
Section: Antioxidant and Anti-listeria Monocytogenes Activitiesmentioning
confidence: 99%
“…However, the hexane extract was the only one that had low activity against bacteria whose MIC value was 1000 µg mL -1 (Table 2). Lemes et al (2018) have recently reported that MIC values below 100 µg mL -1 , between 100 and 500 µg mL -1 and between 500 and 1000 µg mL -1 correspond to promising, moderate and weak activities, respectively, whereas MIC values above 1000 µg mL -1 denote inactivity. Thus, it confirms the antibacterial potential of the most polar extracts from S. odoratissima leaves.…”
Section: Antioxidant and Anti-listeria Monocytogenes Activitiesmentioning
confidence: 99%
“…In order to keep carrying out studies of determination of chemical composition of EO and their activity against white mold (Valadares et al, 2018) and considering the interest of our research group in EO from Citrus species (Estevam et al, 2016;Lemes et al, 2018), the study reported by this paper addresses the chemical composition of EO extracted from Citrus reticulata, C. sinensis and C. deliciosa fruit peel ( Figure 1) and their in vitro inhibitory effect on mycelial growth of S. sclerotiorum.…”
Section: Introductionmentioning
confidence: 99%
“…Leaves EO of C. aurantium grown in Shiraz (south of Iran) showed the presence of limonene, linalool, and trans-β-ocimene as major components and exhibited strong antioxidant activity [65]. EO obtained by cold pressing of C. aurantium fruits with high percentage of limonene (77.90%) and minor percentages of β-pinene (3.40%) and myrcene (1.81%) was inactive against Escherichia coli and Pseudomonas, while moderately active against Stapylococcus aureus [66].…”
Section: Discussionmentioning
confidence: 99%